At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
1) y = 2x + 1
2) y = 2x + 1
Step-by-step explanation:
The parametric equation given is;
x = 1 + ln t and y = t² + 2 at (1, 3)
1) without eliminating the parameter;
Using, x = 1 + ln t ;
dx/dt = 1/t
Using y = t² + 2;
dy/dt = 2t
Slope which is dy/dx is gotten from;
dy/dx = (dy/dt)/(dx/dt)
dy/dx = 2t/(1/t)
dy/dx = 2t²
For x = 1 + In t, at x = 1, we have;
1 = 1 + In t
In t = 0
t = 1
For y = t² + 2, at y = 3, we have;
3 = t² + 2
t² = 3 - 2
t² = 1
t = ±1
Since t = ±1, then;
dy/dx = 2(±1)²
dy/dx = 2
Equation of the tangent is;
y - 3 = 2(x - 1)
y - 3 = 2x - 2
y = 2x - 2 + 3
y = 2x + 1
2) By eliminating the parameter
x = 1 + In t
Let's make t the subject of the equation.
In t = x - 1
t = e^(x - 1)
Let's put e^(x - 1) for t in y = t² + 2
Thus;
y = e^(x - 1)² + 2
y = e^(2(x - 1)) + 2
Thus, parameter has been eliminated
Equation of the tangent is gotten from;
y - y1 = m(x - x1)
m is gradient = dy/dx = 2e^(2(x - 1))
at (1, 3), we have x = 1. Thus;
m = 2e^(2(1 - 1))
m = 2e^0
m = 2
Thus, equation of tangent at (1,3) is;
y - 3 = 2(x - 1)
y - 3 = 2x - 2
y = 2x - 2 + 3
y = 2x + 1
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.